2005
DOI: 10.1074/jbc.m409407200
|View full text |Cite
|
Sign up to set email alerts
|

Pro-angiogenic Signaling by the Endothelial Presence of CEACAM1

Abstract: Here, we demonstrate the expression of carcinoembryonic antigen-related cell adhesion molecule-1 (CEACAM1) in angiogenic sprouts but not in large mother blood vessels within tumor tissue. Correspondingly, only human microvascular endothelial cells involved in in vitro tube formation exhibit CEACAM1. CEACAM1-overexpressing versus CEACAM1-silenced human microvascular endothelial cells were used in migration and tube formation assays. CEACAM1-overexpressing microvascular endothelial cells showed prolonged surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
61
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 45 publications
3
61
0
1
Order By: Relevance
“…Additionally, it was shown that CEACAM1 was enriched in tumor endothelial cells compared with whole lung tumor tissue using a subtracting proteomic mapping technique (Oh et al, 2004). Interestingly, our recent data demonstrate that CEACAM1 overexpression in human micro vascular endothelial cells leads to a significant upregulation of VEGF expression among other pro-angiogenic factors such as Ang1, Ang2, angiogenin and IL-8 (Kilic et al, 2005). This signalling switches endothelial cells to an angiogenic phenotype and demonstrates an inverse action of endothelial CEACAM1 in comparison to epithelial CEACAM1 signalling as demonstrated here by the overexpression of CEACAM1 in the prostate cancer cell line DU-145.…”
Section: Discussionmentioning
confidence: 83%
“…Additionally, it was shown that CEACAM1 was enriched in tumor endothelial cells compared with whole lung tumor tissue using a subtracting proteomic mapping technique (Oh et al, 2004). Interestingly, our recent data demonstrate that CEACAM1 overexpression in human micro vascular endothelial cells leads to a significant upregulation of VEGF expression among other pro-angiogenic factors such as Ang1, Ang2, angiogenin and IL-8 (Kilic et al, 2005). This signalling switches endothelial cells to an angiogenic phenotype and demonstrates an inverse action of endothelial CEACAM1 in comparison to epithelial CEACAM1 signalling as demonstrated here by the overexpression of CEACAM1 in the prostate cancer cell line DU-145.…”
Section: Discussionmentioning
confidence: 83%
“…Because CEACAM1 plays a major role in angiogenesis and vascular integrity (Ergun et al, 2000;Kilic et al, 2005;Muller et al, 2005;Horst et al, 2006;Tilki et al, 2006;Kilic et al, 2007;Horst et al, 2009), we questioned whether the vascular permeability pathway and, more specifically, the eNOS/Akt pathway was dysregulated by CEACAM1. We measured NO release from COS-7 cells co-transfected with CEACAM1-L or CEACAM1-S, eNOS and VEGFR2.…”
Section: Ceacam1 Overexpression Increases Vegfr2-mediated No Productimentioning
confidence: 99%
“…Moreover, Muller and co-workers established that transmembrane CEACAM1-L expressed on endothelial cells was implicated in angiogenic activation by affecting cytoskeletal architecture and integrin-mediated signaling (Muller et al, 2005). Accordingly, CEACAM1 is expressed in newly formed vessels during physiological angiogenesis such as in wound healing and endometrial proliferation, as well as in immature new blood vessels of different tumors (Ergun et al, 2000;Kilic et al, 2005). Downregulation of epithelial CEACAM1-L in prostate intraepithelial neoplasia (PIN) was accompanied by its upregulation in adjacent vasculature, which correlated with vascular destabilization and increased vascularization of prostate tumors (Tilki et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…CEACAM1 semble donc jouer un rôle primordial dans l'intégrité vasculaire et la formation de réseaux capillaires in vivo, particulièrement en situation de néovascularisation [21]. La surexpression de CEACAM1 à la surface de cellules endothéliales induit fortement l'expression de facteurs pro-angiogéniques tels que le VEGF, l'angiopoiétine-1 et -2, l'interleukine-8 (IL-8) ; et, à l'inverse, inhibe la production de facteurs anti-angiogéniques comme le collagène XVIII et l'endostatine [22]. Par ailleurs, CEACAM1 régule l'adhésion des cellules endothéliales sur la matrice extracellulaire via l'activation des protéines de la famille Rho et la voie de signalisation des intégrines [23].…”
Section: Ceacam1 Et L'angiogenèseunclassified